STRATEGI GURU DALAM MENINGKATKAN MINAT BELAJAR SISWA PADA PEMBELAJARAN PPKN KELAS XI DESAIN KOMUNIKASI VISUAL I DI SMK NEGERI 2 BONE - Ramlah, Ramlah; Ilham, Ilham; Ahmad, Ahmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low learning interest of students in Pancasila and Civic Education (PPKn) subject in class XI Visual Communication Design I at SMK Negeri 2 Bone. Learning that tends to be monotonous and less varied causes students to be passive, less attentive, and not actively involved in the learning process. Based on constructivist learning theory, innovative and student-centered learning strategies can increase student engagement and learning interest. This study aims to analyze the strategies used by teachers in increasing student learning interest in PPKn learning. A descriptive qualitative approach was used with research subjects consisting of PPKn teachers and students of class XI Visual Communication Design I. Data were collected through observation, in-depth interviews, and documentation, then analyzed through data reduction, data presentation, and conclusion drawing. The results showed that the teacher applied various learning strategies, including the use of varied methods (group discussions, question and answer, presentations, and Problem Based Learning), utilization of learning media (PowerPoint, videos, images, and textbooks), providing motivation and appreciation, personal approaches, and creating an active and enjoyable learning atmosphere. These strategies had a positive impact on increasing student activeness, participation, and enthusiasm. Although there are still obstacles such as lack of student concentration, use of mobile phones, and differences in student abilities, the strategies implemented are considered effective in increasing student learning interest in PPKn learning.